PENERAPAN TERAPI RELAKSASI GENGGAM JARI DAN NAFAS DALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MACINI - Hestinola Teapon; Sunarti Sunarti; Mardiah Mardiah (CV. Adiba Aisha Amira, 2025)
Background: Hypertension is a chronic condition that can lead to severe cardiovascular complications if not controlled. Nonpharmacological approaches, such as relaxation techniques, can help reduce blood pressure naturally. This study aimed to determine the effect of finger holding and deep breathing relaxation therapy on blood pressure reduction in hypertensive patients. Method: This study used a case study design involving a 66-year-old female patient with hypertension. The intervention was carried out for three consecutive days, 15 minutes per session, including finger-holding and deep breathing exercises. Blood pressure was measured before and after each session. Results: The blood pressure decreased from 150/100 mmHg to 130/80 mmHg after three days of therapy. The patient reported improved relaxation and reduced stress levels. Conclusion: Finger holding and deep breathing relaxation therapy are effective nonpharmacological methods that nurses can implement to help lower blood pressure and improve patients’ quality of life.